2021
DOI: 10.3389/fpsyt.2021.609020
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Intrapartum Factors Associated With Infant Temperament: A Systematic Review

Abstract: Background: Temperament involves individual variations in behavioural tendencies of emotional responses and reactions to stimuli after birth. Because ‘foetal programming' is a strong hypothesis in developing temperament, prenatal and intrapartum factors may be significant determinants of infant temperament. This systematic literature review aims to elucidate the evidence of prenatal and intrapartum predictors, including genetic, biological, environmental, socio-demographic, psychological, and obstetric factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 86 publications
(163 reference statements)
0
16
0
Order By: Relevance
“…Although the association between prenatal anxiety and negative affect has been widely reported, that is not the case with respect to the previous literature on surgency, since some studies have found that it shows a negative association with both prenatal anxiety and negative affect (Enlow et al, 2017 ; Takegata et al, 2021 ). Conversely, our study supports the explanatory models that positively associate negative affect and surgency (Lin et al, 2014 ) as dimensions of infant regulatory capacity: high levels of both variables could imply a risk for regulatory capacity (Gartstein & Rothbart, 2003 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although the association between prenatal anxiety and negative affect has been widely reported, that is not the case with respect to the previous literature on surgency, since some studies have found that it shows a negative association with both prenatal anxiety and negative affect (Enlow et al, 2017 ; Takegata et al, 2021 ). Conversely, our study supports the explanatory models that positively associate negative affect and surgency (Lin et al, 2014 ) as dimensions of infant regulatory capacity: high levels of both variables could imply a risk for regulatory capacity (Gartstein & Rothbart, 2003 ).…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have already highlighted the effects of maternal stress, mainly during the second and third trimesters on infant temperament (Zijlmans et al, 2015 ). For example, prenatal anxiety and depression have been associated with negative maternal report of child effortful control (Miller et al, 2021 ), greater infant negative affect (Pluess et al, 2011 ), difficult temperament (Della Vedova, 2014 ), lower consolation and higher excessive crying (Takegata et al, 2021 ) and greater irritability, reactivity and stress propensity (Gentile, 2017 ). Overall, maternal anxiety and depression during pregnancy serve to increase the risk of having an infant who is less likely to express joy (e.g., smiling and positive affect); is experienced as "difficult" (e.g., crying / fussing excessively); and is more dysregulated or fearful (Erickson et al, 2017 ; Takegata et al, 2021 ; Zijlmans et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Infant development, conceptualized in terms of cognition, motor skills, language, socio-emotional skills, and adaptive behavior, lays the foundation for later outcomes in school [ 1 ], and even into adulthood [ 2 ]. Consistent with the biopsychosocial model [ 3 ], a range of prenatal factors related to the infant’s genetic make-up, environment, socio-demographics, obstetric factors and maternal psychology have been identified as influencing infant development [ 4 ]. Despite this, several promising factors are under-investigated, and particularly those related to the mother’s mental state, feelings of attachment to the unborn baby and others, and previous relational trauma experienced.…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies point to preterm birth or its neurological complications as related to less optimal infant temperamental profile (Takegata et al, 2021), or even to "difficult" temperament (Washington et al, 1986;Larroque et al, 2005). Preterm birth is a multifold risk for child development (Wolke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%